Antimicrobial activity of natural compounds against listeria spp. and their effects on sensory attributes in salmon (Salmo salar) and cod (Gadus morhua). (January 2020) - Pedrós-Garrido, S.; Clemente, I.; Calanche, J.B.; Condón-Abanto, S.; Beltrán, J.A.; Lyng, J.G.; Brunton, N.; Bolton, D.; Whyte, P.
Abstract: The application of natural preservatives on fresh fish has potential to extend shelf-life. In the present study, 8 essential oils (EOs) (lemon, lemongrass, lime, garlic, onion, oregano, thyme and rosemary) and 3 organic acids (OAs) (ascorbic, citric and lactic) were evaluated. The antimicrobial activity of these compounds was tested in-vitro against four confirmed Listeria spp. isolated from retail skin-packed salmon and cod. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were established for each compound. Then, a sensory evaluation was performed by a panel of 'expert assessors' on cooked fish treated with all of the OAs and any 4 EOs with a MIC <0.8%. A series of descriptors were assigned to characterize the combination of each compound with cooked salmon or cod. The highest antimicrobial effect against all Listeria spp. was observed for lactic acid (0.31–2.5%), but treatment with this compound resulted in the development of organoleptically unacceptable changes in salmon or cod. The most acceptable OAs for salmon and cod were ascorbic acid (1.25%) and citric acid (0.63%) respectively, which were shown to enhance certain organoleptic characteristics. The most effective EO against all Listeria strains evaluated was oregano oil (0.2%) and it was considered suitable as a treatment for salmon. In contrast, none of the EOs tested was organoleptically acceptable in combination with cod because of their strong odours and flavours that masked the fresh attributes associated with this fish. Highlights: Lactic acid was the most effective organic acid against evaluated Listeria spp. in-vitro. Oregano showed the highest antimicrobial effect against evaluated Listeria spp. Ascorbic and citric acid proved to be the most suitable organic acids sensorially. None of the 4 essential oils tested in cod were organoleptically acceptable. Oregano oil was the most suitable essential oil from a sensory perspective for salmon.